Diverse yet Representative: Miscellanies of Moves and Steps Depicted in the Move Structure of English Teaching Videos by YouTube Channels from Altered Nations (Universitas Negeri Semarang, 2023)
In an attempt to carry out a rather long been disregarded genre-based topic despite its emerging benefits in facilitating English academic teaching, this study is dedicated to divulging verbal expressions embodying the move structure of English Teaching Videos from different YouTube channels. The study enabled a type of research innate to the nature of qualitative research, which is content analysis. The investigated data were ten different YouTube videos that originated nationally and internationally. The frameworks used to tailor the research instrument (observational sheet) here is one from Chang and Huang (2015) regarding the move structure of inspirational YouTube content. The result displayed that the utterances in the entire dataset fulfilled most of Chang and Huang’s moves. Specifically, the move structure in national and international English teaching videos transpired in assorted utterances from the data. The chief notion drawn from this research is the idea that the whole data have a malleable yet archetypal move structure that characterized them as English teaching YouTube videos.